Amygdala subnuclei development in adolescents with autism spectrum disorder: Association with social communication and repetitive behaviors. Issue 8 (1st August 2021) - Seguin, Diane; Pac, Sara; Wang, Jianan; Nicolson, Rob; Martinez‐Trujillo, Julio; Duerden, Emma G.
Abstract: Introduction: The amygdala subnuclei regulate emotional processing and are widely implicated in social cognitive impairments often seen in children with autism spectrum disorder (ASD). Dysregulated amygdala development has been reported in young children with ASD; less is known about amygdala maturation in later adolescence, a sensitive window for social skill development. Methods: The macrostructural development of the amygdala subnuclei was assessed at two time points in a longitudinal magnetic resonance imaging (MRI) study of adolescents with ASD ( n = 23) and typically‐developing adolescents ( n = 15) . In adolescents with ASD, amygdala subnuclei growth was assessed in relation to ASD symptomatology based on standardized diagnostic assessments. Participants were scanned with MRI at median age of 12 years and returned for a second scan at a median age of 15 years. The volumes of nine amygdala subnuclei were extracted using an automatic segmentation algorithm. Results: When examining the longitudinal data acquired across two time points, adolescents with ASD had larger basolateral amygdala (BLA) nuclei volumes compared to typically developing adolescents ( B = 46.8, p = 0.04). When examining ASD symptomatology in relation to the growth of the amygdala subnuclei, reciprocal social interaction scores on the ADI‐R were positively associated with increased growth of the BLA nuclei ( B = 8.3, p < 0.001). Growth in the medial nucleus negatively predicted the communication ( B = −46.9, p = 0.02) and social ( B = −47.7, p < 0.001) domains on the ADOS‐G. Growth in the right cortical nucleus ( B = 26.14, p = 0.02) positively predicted ADOS‐G social scores. Central nucleus maturation ( B = 29.9, p = 0.02) was associated with the repetitive behaviors domain on the ADOS‐G. Conclusions: Larger BLA volumes in adolescents with ASD may reflect underlying alterations in cellular density previously reported in post‐mortem studies. Furthermore, findings demonstrate an association between regional growth in amygdala subnuclei volumes and ASD symptomatology. Improved understanding of the developmental trajectories of the amygdala subnuclei may aid in identifying key windows for interventions, particularly for social communication, in adolescents with ASD. Abstract : Amygdala subnuclei maturation was examined in adolescents with and without ASD. The volumes of the BLA nuclei were larger in adolescents with ASD compared to controls. BLA, cortical, and medial nuclei predicted social and/or communication skills. Larger central nuclei volumes positively predicted repetitive behaviors.